Correlation Analysis of Lemon, IDS, and Wilson Scores in Assessing Intubation Difficulty in Patients Undergoing General Anesthesia - Sinaga, Ade; Hamdi, Tasrif; Tanjung, Qadri Fauzi (CoinReads Media Prima, 2024)
Introduction: The act of intubating with an endotracheal tube is a definitive airway management technique that provides maximal protection against the occurrence of aspiration of stomach contents or fluids. Some studies recommend the use of a head pillow to improve the laryngoscopic view by enhancing the occipito-atlanto-axial angle and enlarging the submandibular space. The aim of this study was to find out comparison of the level of difficulty of intubation in intubation techniques with and without the use of pillows. Methods: The design of this study was a randomized cross-sectional study with two research groups conducted to compare the difficulty levels of intubation using the technique with and without a pillow. Results: Patients without a pillow often required a little assistance during intubation, while the majority of patients using a pillow were easily intubated. However, no significant difference was found between the two groups (p>0.05). Patients intubated without a pillow had an average score of 15.9±1.6, while those intubated with a pillow had an average score of 10.8±1.8, showing a significant difference between the two groups (p<0.05). Using the Cormack-Lehane score, most patients without a pillow were at grade 2, while the majority of patients with a pillow were at grade 1. A significant difference was found between the two groups (p<0.05). Conclusion: Patients intubated without a pillow often required a little assistance, while the majority of patients intubated with a pillow were easily intubated; however, no significant difference was found between the two groups (p>0.05).